Improved Visualization of Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae)—Part I: Morphological Features for Sex Determination of Multiple Stadia - J. F. Esquivel; T. L. Crippen; L. A. Ward (Psyche: A Journal of Entomology)
The lesser mealworm, Alphitobius diaperinus (Panzer), is a perennial pest of poultry facilities and known to transmit pathogens of poultry and humans. Ongoing research examining reservoir potential of A. diaperinus revealed the need for a comprehensive, user-friendly guide for determining sex of A. diaperinus at different stadia. This paper is unique in providing a comprehensive illustrated guide of characters used for differentiation of sexes in A. diaperinus.